Use of direct oral anticoagulants in cerebral venous thrombosis: a systematic review. Issue 8 (December 2020) - Sheng, Sen; Nalleballe, Krishina; Pothineni, Naga V.; Sharma, Rohan; Brown, Aliza; Elkhider, Hisham; Ranabothu, Saritha; Kapoor, Nidhi; Patrice, Kelly-Ann; Onteddu, Sanjeeva
Abstract : N/A: We are here to review the efficacy and safety of direct oral anticoagulants (DOACs) in the treatment of Cerebral Venous Thrombosis (CVT). A search strategy was developed with a research librarian. All published articles including trials, studies, case series, and case reports were reviewed from NCBI/PubMed up to May 2019 by two independent reviewers. A total of 11 studies were identified, which included 70 patients with CVT on DOACs. After 6 months follow-up more than 86.7% of these patients had a good outcome on the Modified Rankin Scale (mRS) of 0–1 at 6 months and no recurrence of venous thromboembolic events (VTE) at 12 months. Recanalization rate at 6 months varied from 55 to 100%. Only two patients had a side effect of minor bleeding because of DOAC usage. Although the current American Heart Association/American Stroke Association and European Stroke Organization guidelines do not endorse the use of DOACs for treatment of CVT because of lack of evidence from large randomized clinical trials, Use of DOACs in CVT appears to be well tolerated and efficacious with favorable outcomes. Further evidence is needed to establish their use in CVT. Abstract : Supplemental Digital Content is available in the text